An investigation of the relationship between the psychological needs, values and elements of personal adjustment of a group of male juvenile delinquents in a reformatory and its usefulness in a dimensional framework as a basis for a differential rehabilitation programme - Botha, Marthinus Jacobus (School of Education, 2023)
A considerable mass of knowledge about the ethology, prevention and treatment of juvenile delinquency has given rise to a variety of treatment programmes over the two decades since 1960. These treatment approaches range from the community-oriented, non-restrictive methods to the strict incarceration of juvenile offenders. Rather than having solved the problems relating to the treatment of delinquents, the knowledge and efforts have created more questions than answers as to what the best approaches should be. In spite of all the efforts by correctional institutions to "reform" the young people placed in their care, Wilson (1975) states that these institutions are not effective in reducing. Whatever else they may accomplish The treatment success rate, usually based only on recidivism statistics, shows a steady decline to below thirty per cent in some American programmes (Lipton 1975). Dinitz et al (1980) found the effectiveness of correctional programmes to be "ineffective at best and devastatingly negative at v:orst" ( p149).